THE PROBLEM OF ASSESSMENT IN THE SYSTEM OF HIGHER EDUCATION IN THE 21ST CENTURY (EDUCATION IN THE 21ST CENTURY, 2023)
The integration of artificial intelligence (AI) in the assessment process has emerged as a significant development in higher education. This scientific paper explores the implications of AI-based assessment methods in the context of higher education and discusses their advantages, limitations, and ethical considerations. The paper reviews relevant literature to examine the application of AI systems in evaluating students' knowledge, focusing on their impact on efficiency, objectivity, personalized learning experiences, and immediate feedback provision. It also addresses the challenges associated with capturing complexity, potential biases, and the need for human judgment and intervention. Ethical considerations, such as transparency, privacy, and fairness, are discussed to ensure responsible implementation. The paper presents a case example of an interview with educators, highlighting their perspectives on AI-based assessment. Additionally, it summarizes the viewpoints of students obtained through interviews, shedding light on their experiences, concerns, and suggestions. The analysis of the interviews provides insights into the integration of AI-based assessment while maintaining a balanced approach that values human expertise. Based on the findings, this paper proposes recommendations for educators and institutions to effectively leverage AI-based assessment methods, ensuring a comprehensive and ethical approach that enhances student learning experiences and outcomes. Overall, this paper contributes to the growing body of knowledge on the use of AI in higher education assessment, providing valuable insights for educators, policymakers, and researchers in navigating the challenges and opportunities presented by the age of artificial intelligence.
Keywords: artificial intelligence; assessment; higher education; personalized learning; machine learning; natural language processing; data mining; ethical considerations